PENGARUH POLITICAL MOTIVATION DAN TAXATION MOTIVATION TERHADAP KECURANGAN PELAPORAN KEUANGAN - Dewi Arimbi (Master of Accounting Universitas Trunojoyo Madura, 2015)
The purpose of this research is to find empirical evidence about the factors that motivate the occurrence of fraudulent financial reporting. These factors are tested in this research was political motivation and motivation taxation. This research uses secondary data on companies listed in the Indonesia Stock Exchange. Data companies that commit fraud is proven enterprise sanctioned Indonesian Capital Market and Financial Institution Supervisory Agency and Financial Service Authority (FSA) in 2001-2014, the sanctions contained elements of fraud. The number of samples analyzed were 112 companies consisting of 56 companies of fraud and non-fraud 56 companies. Then the data analysis which includes descriptive statistics, multicoloniarity, and logistic regression. The results shows that taxation motivation has a significant effect on fraudulent financial reporting, while political motivation had no affect on the fraudulent financial reporting.